Cognitive and behavioural aspects of Prader–Willi syndrome. Issue 2 (March 2015) - Rice, Lauren J.; Einfeld, Stewart L.
Abstract : Purpose of review: To provide a review of the recent advances in the diagnosis and treatment of psychiatric disorders in Prader–Willi syndrome (PWS). Recent findings: Research in the last 12 months has provided a descriptive prognosis of psychosis in PWS and highlighted the possible genes associated with the increased risk of psychosis for those with maternal uniparental disomy (mUPD). Several studies investigating social and communication skills have shown people with PWS to have difficulty with core, receptive and expressive language skills, interpreting emotional valence in faces, playing with children of their own age, understanding personal space and a developmental delay in the theory of mind. These social and communication deficits are often more pronounced in those with mUPD. Two recent clinical trials of oxytocin provide mixed results and highlight the need for an improved understanding of the neurobiological characteristics of the PWS brain. A recent pilot study suggests N -acetylcysteine may be a viable treatment for skin picking. Summary: Recent advances have contributed to our understanding of the emotional and behavioural problems associated with PWS, and provided directions for further research.